Digital Green Finance, FinTech Innovation, and Corporate Environmental Performance: Evidence from Global Firms - Perera, Vidura; Wasantha , Neel; Dissanayake , Tharindu; Bandara , Aruna Ishara; Gunasena , Daham; Kumara , Nuwan Pushpa; Jayawickrama , Sanjeewa; Madurapperuma , Wasanthi; Wanninayake, Bandara (International Journal of Energy Economics and Policy, 2026)
Digital green finance (DGF) the combination of green financial tools with FinTech systems like blockchain-based bonds, AI-driven credit scoring, and digital disclosure platforms—has become an important way to get climate-aligned capital moving. However, its efficacy in the context of economic policy uncertainty (EPU) remains empirically insufficiently examined. This study investigates the correlation between green finance (GF) and corporate environmental performance (CEP), as well as the influence of digitalization and policy instability on this relationship. We use a balanced panel of 1,280 listed non-financial companies from nine economies (the US, the UK, Germany, France, the Netherlands, Sweden, Japan, Canada, and China) between 2012 and 2024. We use two-way fixed effects, instrumental variables (IV/2SLS), propensity score matching with difference-in-differences (PSM-DID), triple interaction models, and sectoral heterogeneity tests. We find that GF significantly improves CEP by giving companies credible decarbonization capital and making environmental disclosure stronger. This is in line with stakeholder theory and the resource-based view. However, this effect diminishes at elevated EPU levels, consistent with real options theory: policy volatility increases risk premiums and postpones irreversible green investment. Digitalization significantly enhances the GF–CEP connection and partially mitigates the dampening influence of EPU. This suggests that FinTech-facilitated transparency, traceability, and monitoring bolster the credibility and sustainability of green investment, even amid volatile policy contexts. The effect is strongest in sectors that emit a lot of pollution and are going through a lot of changes, but these sectors are also the most likely to be affected by policy uncertainty. These results show that DGF is not only a way to make things more efficient, but also a way to keep institutions stable. The research provides novel cross-national causal evidence regarding the interplay of finance, technology, and policy in shaping firms’ environmental outcomes on a large scale.